2022
DOI: 10.3390/ijms232314631
|View full text |Cite
|
Sign up to set email alerts
|

Tirzepatide: A Systematic Update

Abstract: Tirzepatide is a new molecule capable of controlling glucose blood levels by combining the dual agonism of Glucose-Dependent Insulinotropic Polypeptide (GIP) and Glucagon-Like Peptide-1 (GLP-1) receptors. GIP and GLP1 are incretin hormones: they are released in the intestine in response to nutrient intake and stimulate pancreatic beta cell activity secreting insulin. GIP and GLP1 also have other metabolic functions. GLP1, in particular, reduces food intake and delays gastric emptying. Moreover, Tirzepatide has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…However, the chosen doses of GLP‐1RAs might not be the reason that we did not find an impact of GLP‐1RAs in increasing heart rate because the GLP‐1RAs doses included in this study were dulaglutide 0.75 to 1.5 mg and semaglutide 1.0 mg per week, which are the maximum dosages widely used in clinical practice to treat diabetes mellitus. TZP has better efficacy in reducing HbA1c and body weight and increasing gastrointestinal adverse events than GLP‐1RAs, 15,21 which might indicate that the chosen TZP doses have a stronger activation effect on GLP‐1 receptors 44 . Additionally, GIP could increase heart rate directly, and its potential impact on vasodilation may also lead to an increase in heart rate 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the chosen doses of GLP‐1RAs might not be the reason that we did not find an impact of GLP‐1RAs in increasing heart rate because the GLP‐1RAs doses included in this study were dulaglutide 0.75 to 1.5 mg and semaglutide 1.0 mg per week, which are the maximum dosages widely used in clinical practice to treat diabetes mellitus. TZP has better efficacy in reducing HbA1c and body weight and increasing gastrointestinal adverse events than GLP‐1RAs, 15,21 which might indicate that the chosen TZP doses have a stronger activation effect on GLP‐1 receptors 44 . Additionally, GIP could increase heart rate directly, and its potential impact on vasodilation may also lead to an increase in heart rate 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Research has shown that TZP is more efficient in lowering blood glucose and reducing body weight than GLP-1RAs, and potentially decreases the risk of cardiovascular events. 15,17,18 However, the published TZP product monograph showed that it could cause a mean increase in heart rate from 2 to 4 bpm. 19 Although previous studies had revealed a dose-response relationship of TZP in its effect on glucose control and weight loss, [20][21][22] a summary of the heart rate data from different studies, with specific effect and confidence intervals (CIs) and data on a possible dose-response relationship with regard to heart rate, were not provided in the monograph.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…which analysed the benefits of a novel medication, tirzepatide, a molecule that acts by the dual agonism of GLP-1/GIP receptors. Tirezepatide’s efficacy in reducing blood glucose, weight, and blood pressure values was confirmed in five clinical trials in patients with type 2 diabetes mellitus, while in non-diabetic obese patients, a weekly administration of the drug, in various concentrations, produced remarkable results in reducing body weight [ 6 ].…”
mentioning
confidence: 99%